PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI LEMBAGA PEMASYARAKATAN KELAS I CIPINANG DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Rina Yulianti; Endang Tri Pujiastuti; Sukardi; Ardi Kusmara (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this study was to determine the impact of compensation and work stress on the employee work satisfaction with work motivation as an intervening variable in Cipinang Class I Jail, Jakarta. This study was conducted using a saturated sample. The analysis tool used is SEM (Structural Equation Modeling). The test result showed that 1) Compensation had a positive and significant impact on work satisfaction meaning that the increasing compensation increased employee satisfaction. 2) Work stress had a positive and significant impact on employee work satisfaction meaning that the increasing work stress would also increase employee work satisfaction. 3) Compensation had a positive and significant impact on employee motivation meaning that the increasing compensation increased employee motivation. 4) Work stress had no positive yet insignificant impact on employee motivation meaning that increased employee stress caused work satisfaction to not necessarily increase. 5) Work motivation had a positive and significant impact on employee work satisfaction meaning that increasing motivation increased employee work satisfaction. 6) Work motivation mediated work compensation had a positive and significant impact on employee satisfaction meaning that the motivation given by the leaders could increase work satisfaction. 7) Work motivation did not mediate work stress and was insignificant for employee work satisfaction meaning that work motivation did not necessarily affect employee work stress.